CULTURAL VALUES IN THE DANCE OF PATTUDDUQ TOWAINE IN POLEWALI MANDAR, WEST SULAWESI PROVINCE - Ansaar, Ansaar (Kementerian Pendidikan dan Kebudayaan, 2020)
This study is the research result which aims to examine the cultural values contained in the dance of pattudduq towaine, either related to the materials and equipment used or the dance movement reflections. This research is a descriptive qualitative study with data collection techniques in the form of observation, interview, library research as secondary data. The result shows that the dance of pattudduq towaine is one of dances in West Sulawesi which is performed by female dancers with graceful movements. This dance is famous in West Sulawesi and is often performed at various events, such as welcoming events, art performances, and cultural festivals. Several cultural values contain in the materials and equipment in the dance of pattudduq towaine, namely aesthetic value, artistic value (music value), cohesiveness value, and science/knowledge value. Meanwhile, the cultural values reflected on the dance movements of pattudduq towaine include entertainment value, cohesiveness/togetherness value, softness value, aesthetic/beauty value, religious value, personality value, and educational value.Â